Simulação clínica sobre cateterismo intermitente limpo para educação em saúde de cuidadores de crianças com disfunções miccionais - Torquato, Rebecca Camurça (2023)
Voiding dysfunction results from impairment of one or more elements of the urinary elimination process and clean intermittent catheterization is the main treatment for some of these dysfunctions. Nursing plays a role in the rehabilitation process of these patients. When these patients are children, guidance should be given, especially to their caregivers. One of the strategies aimed at health education for caregivers is clinical simulation, because it is a tool capable of promoting a safe and controlled learning environment. Thus, this research aimed to build a clinical simulation scenario on the management of clean intermittent catheterization for the teaching-learning process of caregivers of children with voiding dysfunctions. This is a methodological study carried out in two stages, from January 2022 to April 2023. The first stage consisted of building a clinical case regarding the theme of clean intermittent catheterization. The second stage was the construction of the clinical simulation scenario, following the methodological framework proposed by Nogueira, Domingues and Bergamasco and the "Standards of Best Practice in Simulation" of the International Nursing Association of Clinical and Simulation Learning. Because the study was not with human beings, submission to the Research Ethics Committee was not necessary. In the elaboration of the scenario, the clinical case constructed contextualized the development of the simulated activity. The following items were contemplated in the construction of the simulated scenario: planning, learning objectives, structure and format of the simulation, scenario description and fidelity, briefing, debriefing, and evaluation. In the learning objectives, the management of the procedure was considered, which included possible complications and hand hygiene. In the structure and format of the simulation, the environment, materials, simulators, human resources and number of participants are described. In the description of the activity, a decision-making flowchart of the simulation scenario was elaborated and this was of low fidelity. In the briefing and debriefing, a script was built to standardize these steps. In the evaluation, the use of instruments with caregivers was considered. The final construct of the simulation scenario lasted 1 hour and 30 minutes, starting with the proposal to apply the adapted questionnaire on knowledge about CIL. Its general learning objective was to manage clean intermittent catheterization in children. The desirable characteristics were identified for the selection of facilitators and the realization of the simulated activity individually. The modality was clinical simulation using two low-fidelity simulators, being carried out in a nursing outpatient clinic or other services that provide care to children with voiding dysfunction. The prepared clinical case guided the conduction of the simulated activity and the briefing and debriefing script contains questions to direct such steps. Finally, validated instruments were selected to carry out the simulation evaluation stage. It is possible to build a clinical simulation scenario to promote health education for these caregivers. This teaching-learning strategy can provide active learning and should be further explored by nurses. The application of this simulation will be carried out in a later study.